COSMIC-S: A Photometric Catalog of Observed Stars in the Small Magellanic Cloud - Antonio Franco; Achille A. Nucita; Francesco De Paolis; Francesco Strafella (The Astrophysical Journal Supplement Series)
The Dark Energy Camera (DECam) is a wide-field instrument mounted on the 4 m V. Blanco Telescope (Cerro Tololo Inter-American Observatory). Its impressive technical characteristics make it one of the most suitable ground-based telescopes for the production of accurate stellar photometry, even toward crowded regions such as the Magellanic Clouds. We analyzed DECam images acquired from 2018 February to 2020 January toward the Small Magellanic Cloud. We performed a point-spread function photometry by using the SExtractor and PSFEx tools and producing a comprehensive photometric catalog in the Sloan Digital Sky Survey system, considering the gri filters. Then, we present COSMIC-S, a photometric catalog consisting of 10,971,906 sources, including gri magnitudes with a mean error 〈 σ _m 〉 ≃ 0.04 mag. A total of 2,456,434 sources have good photometry in all three bands. The catalog appears virtually complete to m  ≃ 22, with a limiting magnitude m  ≃ 25. We derived the color–magnitude and color–color diagrams in order to prove the goodness of the catalog.